1994
DOI: 10.1007/bf00711587
|View full text |Cite
|
Sign up to set email alerts
|

Isolated dihydroxyacetonephosphate acyltransferase deficiency presenting with developmental delay

Abstract: A boy aged 21 months who was being investigated for developmental delay and failure to thrive was found to have punctate epiphyseal calcification. He had no evidence of rhizomelic shortening of the limbs or cataracts. Investigation revealed defective plasmalogen synthesis due to isolated deficiency of dihydroxyacetonephosphate acyltransferase (DHAP-AT). The parents were consanguineous and a sister was similarly affected, suggesting autosomal recessive inheritance. Hitherto, recessively inherited isolated DHAP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The girl's low activity of DHAPAT and deficient de novo plasmalogen synthesis in association with normal alkyl-DHAP synthase activity, phytanic acid concentration, and 3-oxoacyl-CoA thiolase protein are consistent with RCDP type 2 due to isolated DHAPAT deficiency. Only a few cases of chondrodysplasia punctata have been described previously with this isolated enzyme deficiency (Wanders et al 1992, Barr et al 1993, Clayton et al 1994, Hebestreit et al 1996. Those patients showed clinical heterogeneity: both rhizomelic forms with severe outcome and non-rhizomelic variants with a relatively mild clinical course have been described (Wanders et al 1992, Barr et al 1993, Clayton et al 1994, Hebestreit et al 1996.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The girl's low activity of DHAPAT and deficient de novo plasmalogen synthesis in association with normal alkyl-DHAP synthase activity, phytanic acid concentration, and 3-oxoacyl-CoA thiolase protein are consistent with RCDP type 2 due to isolated DHAPAT deficiency. Only a few cases of chondrodysplasia punctata have been described previously with this isolated enzyme deficiency (Wanders et al 1992, Barr et al 1993, Clayton et al 1994, Hebestreit et al 1996. Those patients showed clinical heterogeneity: both rhizomelic forms with severe outcome and non-rhizomelic variants with a relatively mild clinical course have been described (Wanders et al 1992, Barr et al 1993, Clayton et al 1994, Hebestreit et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation analysis in eight individuals from five families has recently revealed five types of mutations (Ofman et al 1998). Three affected children in another Yemeni family (Clayton et al 1994, Sztriha et al 1997, Ofman et al 1998) had the same mutation as the reported girl. The arginine residue, which has been substituted by a histidine at position 211 (R211H) in these cases, is conserved in several species, suggesting an important role of this residue for the catalytic activity of the enzyme (Ofman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient has all these features except rhizomelia. A phenotype with GNPAT mutation without rhizomelia and cataracts has previously been described [Clayton et al, 1994]. Six additional patients with RCDP2 and RCDP3 due to GNPAT mutations have been identified [Itzkovitz et al, 2012].…”
Section: Discussionmentioning
confidence: 99%